The Lorax (2012) [videorecording (DVD)] - Renaud, Chris; Balda, Kyle; DeVito, Danny; Helms, Ed; Efron, Zac; Swift, Taylor, 1989-; White, Betty, 1922-; Seuss, Dr (Universal Studios Home Entertainment, 2012)
In a place where the brown Bar-ba-loots frisk and the Humming-Fish splash around, you will find the Lorax. The Lorax speaks of the trees, which the Once-ler is chopping down as fast as he pleases. Will the Once-ler change his destructive ways and heed the wise warnings of the Lorax?